Prototype Smart Home Pengendali Lampu Dan Gerbang Otomatis Berbasis IoT Pada Sekolah Islam Pelita Insan Menggunakan Microcontroller Nodemcu V3 - Wiyanto, Wiyanto; Oktavianti, Yayan (UNISTEK, 2021)
Current technological developments have penetrated into human life, such as the development of a smart home called a smart home, that can provide convenience, comfort, safety and efficiency for users. Internet of Things (IoT) can be used in smart homes to control electronic equipment such as lights and home gates. This research designed an automatic controller and light gate based IoT (Internet of Things) smart home system using a NodeMCU microcontroller with a prototype method that aims to save electricity, make it effective and efficient, and make it easier for schoolkeepers to turn on lights and control the gate automatically through the Google assistant. The results of this study are in the form of an automatic light and gate control system using the Google assistant application based on the Internet of Things Using a NodeMCU v3 microcontroller. Can be concluded with the automatic light and gate control system using the google assistant application by giving commands to the google assistant connected to the NodeMCU V3 microcontroller, it can make it easier for school administrators to make efficient and efficient lights or gates using the google assistant application and can facilitate school administrators to maintain the security of the Internet-based school of Things.